MARKETING RESEARCH OF THE MEDICINE MARKET FOR THE TREATMENT OF BREAST CANCER IN UKRAINE - Rafalska , Yaroslava; Kosyachenko , Kostyantin (The Ukrainian Scientific Medical Youth Journal, 2021)
the article presents the results of the study of the marketing market of medicines for the treatment of breast cancer in Ukraine during 2019-2020. Medicine treatment schemes based on a clinical protocol were analyzed. On December 1, 2019, 184 drugs were registered for the treatment of breast cancer in Ukraine, and on December 1, 2020 - 194. In 2020, the largest share among of the studied drugs belongs to the group of antineoplastic and immunomodulatory drugs - 82.0 %, and the group of drugs that affect the musculoskeletal system - 18.0 %. On December 1, 2020, drugs were represented by 43 manufacturers, of which 18.6 % were Ukrainian and 81.4 % were foreign. Among Ukrainian companies, the primacy belongs to Pharmex Group LLC (4.1 %), Teva Ukraine LLC (3.1 %) and Farmak JSC (2.6 %). The largest share of foreign suppliers occupies Great Britain - 26.3 %, Switzerland and India by 11.9 %. At that time, in 5 pharmacotherapeutic groups (L01AA01, L01BA01, L01CA04, L01XC07, M05BA03) is not represented by any drug Ukrainian manufacturer. Analysis of the assortment of drugs for the treatment of breast cancer by dosage form in 2020 showed that the main share (35.6 %) is represented by concentrate for solution for infusion, 21.6 % - tablets and 20.6 % - lyophilisate for solution for infusion. Other dosage forms form a total of 22.2 % of the total assortment of drugs, studied in the Ukrainian market.